Effects of mixed-phase copper oxide nanofibers in ZnO dye-sensitized solar cells on efficiency enhancement - Karakade Kaewyai (2018)
Copyright © 2017 American Scientific Publishers All rights reserved. The mixed phases of copper oxide nanofibers (CuO and Cu2O) were introduced as a double layer in photoelectrodes of ZnO based dye-sensitized solar cells (DSSCs). In this study, the various masses of copper oxide nanofibers (0-5.70 mg) were prepared in viscous solution form and coated on 1 cm2 ofthe ZnO layer. The ZnO based DSSCs with different surface densities of copper oxide layers (0-5.70 mg/cm2) were fabricated and investigated for power conversion efficiency, photocurrent, photovoltage, electrical properties and optical properties. The highest photoconversion efficiency of 1.87% and the highest current density of 6.93 mA/cm2were observed for copper oxide nanofibers at a density of 3.42 mg/cm2. The efficiency enhancement of the ZnO DSSCs coating by mixed-phase copper oxide nanofiber layer is related to an increase in charge carrier density that must be faster than the charge recombination rate. This high performance can be elucidated by the large internal surface area for dye adsorption and by the wide photon absorption range. Therefore, the double layer structure can serve as the active photo layer. This study shows that the composite structure electrode is the best approach compared to a single structure electrode for improving the cell efficiency of DSSCs.